Photoelectrochemical Hydrogen Production - van de Krol, Roel; Grätzel, Michael (Electronic Materials: Science & Technology, 2012)
Photoelectrochemical Hydrogen Production describes the principles and materials challenges for the conversion of sunlight into hydrogen through water splitting at a semiconducting electrode. Readers will find an analysis of the solid state properties and materials requirements for semiconducting photo-electrodes, and a detailed description of the semiconductor/electrolyte interface and the photo-electrochemical (PEC) cell.  Experimental techniques to investigate both materials and PEC device performance are outlined, followed by an overview of the current state-of-the-art in PEC materials and devices, and combinatorial approaches towards the development of new materials. Finally, the economic and business perspectives of PEC devices are discussed, and promising future directions indicated. This book also: Emphasizes defect chemical aspects of metaloxide photoelectrodes Provides chapters dedicated to state-of-the-art materials and devices, measurement techniques, and combinatorial techniques to find new photoelectrode materials Offers valuable discussion of business perspectives and economic outlook Photoelectrochemical Hydrogen Production is a one-stop resource for scientists, students and R&D practitioners starting in this field,providing both the theoretical background as well as useful practical information on photoelectrochemical measurement techniques. Experts in the field benefit from the chapters on current state-of-the-art materials/device sand future directions.  .